Answer:
The word "Of" in an equation is interpreted to be multiplication. Also, you must move the decimal two places to the left to change a percent to a decimal.
1. 20 * .12 = 2.4
2. .3 * 70 = 21
3. 300 * .25 = 75 Blue marbles
4. 40 * .35 = $14
Answer:
65000
Step-by-step explanation:
Answers: height, "h", of a triangle: <span> h = 2A / (b₁ + b₂) .
___________________________________________________ </span>
Explanation:
__________________________________________________
The area of a triangle, "A", is equal to (1/2) * (b₁ + b₂) * h ;
or: A = (1/2) * (b₁ + b₂) * h
or: write as: A = [(b₁ + b₂) * h] / 2 ;
___________________________________________
in which: A = area of the triangle;
b₁ = length of one of the bases
of the triangle ("base 1");
b₂ = length of the other base
of the triangle ("base 2");
h = height of the triangle;
____________________________________________________
To find the height of the triangle, we rearrange the formula to solve for "h" (height); assuming that all the units are the same (e.g. feet, centimeters); if no "units" are given, then the assumption is that the units are all the same.
We can use the term "units" if desired, in such cases; in which the area, "A" is measured in "square units"; or "units²",
_________________________________
So, given our formula for the "Area, "A"; of a triangle:
_________________________________________________
A = [(b₁ + b₂) * h] / 2 ; we solve for "h" in terms of the other values; by isolating "h" (height) on one side of the equation.
If we knew the other values; we plug in the those other values.
______________________________________________
Given: A = [(b₁ + b₂) * h] / 2 ;
Multiply EACH side of the equation by "2" ;
_________________________________________
2*A = { [(b₁ + b₂) * h] / 2 } * 2 ;
_________________________________________
to get:
_________________________________________
2A = (b₁ + b₂) * h ;
_____________________________________________________
Now, divide EACH side of the equation by: "(b₁ + b₂)" ; to isolate "h"
on one side of the equation; and solve for "h" (height) in terms of the other values;
_____________________________________
2A / (b₁ + b₂) = [ (b₁ + b₂) * h ] / (b₁ + b₂);
______________________________________
to get:
_______________________________________________
2A / (b₁ + b₂) = h ; ↔<span> h = 2A / (b₁ + b₂) .
__________________________________________________</span>
If you would like to know if (0, 3) is a solution to the equation y = x + 3, you can find this using the following step:
(0, 3) = (x, y)
x = 0
y = 3
y = x + 3
3 = 0 + 3
3 = 3
Result: (0, 3) is a solution to the equation y = x + 3.